Optimization of contactless transformer coupling transmission system by Taguchi method. Issue 5 (9th April 2017) - Cheng, Chin-Hsing; Cheng, Po-Jen; Zeng, Yong-Zhen
ABSTRACT: A contactless transformer coupling (CTC) transmission system transmits electric energy via an alternating magnetic field through an air-gap. The transmitted power can be enhanced by the application of resonant effects. Transmitting and receiving coils are usually single layer solenoids with series capacitors, which, in combination, allow the receiving element to be tuned to the required transmitter frequency. An input DC source is used to obtain high-frequency AC signal through the standardized half-bridge DC/AC switching circuit. Further, the high-frequency signal passes through matching transformer and contactless coupling induction coil, which can be considered as an isolated input and output stage. Coupling must be tight to achieve high efficiency. This paper then applies the methods of Taguchi parameter design forthe contactless transformer coupling transmission system, which enhances the output voltage, loss factor, and output efficiency of the transmission system. The results of measurement verify the feasibility of this structure in the experiment.